Identification of proteins associated with clinical and pathological features of proliferative diabetic retinopathy in vitreous and fibrovascular membranes. - Ingeborg Klaassen; Ewout W de Vries; Ilse M C Vogels; Antoine H C van Kampen; Machteld I Bosscha; David H W Steel; Cornelis J F Van Noorden; Sarit Y Lesnik-Oberstein; Reinier O Schlingemann (PLoS ONE, 2017)
To identify the protein profiles in vitreous associated with retinal fibrosis, angiogenesis, and neurite formation in epiretinal fibrovascular membranes (FVMs) in patients with proliferative diabetic retinopathy (PDR).Vitreous samples of 5 non-diabetic control patients with vitreous debris and 7 patients with PDR membranes were screened for 507 preselected proteins using the semi-quantitative RayBio® L-series 507 antibody array. From this array, 60 proteins were selected for a custom quantitative antibody array (Raybiotech, Human Quantibody® array), analyzing 7 control patients, 8 PDR patients with FVMs, and 5 PDR patients without FVMs. Additionally, mRNA levels of proteins of interest were measured in 10 PDR membranes and 11 idiopathic membranes and in retinal tissues and cells to identify possible sources of protein production.Of the 507 proteins screened, 21 were found to be significantly elevated in PDR patients, including neurogenic and angiogenic factors such as neuregulin 1 (NRG1), nerve growth factor receptor (NGFR), placental growth factor (PlGF) and platelet derived growth factor (PDGF). Angiopoietin-2 (Ang2) concentrations were strongly correlated to the degree of fibrosis and the presence of FVMs in patients with PDR. Protein correlation analysis showed PDGF to be extensively co-regulated with other proteins, including thrombospondin-1 and Ang2. mRNA levels of glial-derived and brain/derived neurotrophic factor (GDNF and BDNF) were elevated in PDR membranes. These results were validated in a second study of 52 vitreous samples of 32 PDR patients and 20 control patients.This exploratory study reveals protein networks that potentially contribute to neurite outgrowth, angiogenesis and fibrosis in the formation of fibrovascular membranes in PDR. We identified a possible role of Ang2 in fibrosis and the formation of FVMs, and of the neurotrophic factors NRG1, PDGF and GDNF in neurite growth that occurs in all FVMs in PDR.